To Make Our World Anew, Volume II : a History of African Americans Since 1880. - Kelley, Robin D. G. (Oxford University Press, USA, 2005)
The two volumes of Kelley and Lewis's To Make Our World Anew integrate the work of eleven leading historians into the most up-to-date and comprehensive account available of African American history, from the first Africans brought as slaves into the Americas, right up to today's black filmmakers and politicians. This second volume covers the crucial post-Reconstruction years and traces the migration of blacks to the major cities. It describes the remarkable birth of the Harlem Renaissance, the hardships of the Great Depression, and the service of African Americans in World War II. Readers witn.